PENGARUH MEDIA KINCIR ANGKA TERHADAP KEAKTIFAN BELAJAR PADA OPERASI HITUNG PENJUMLAHAN MATEMATIKA PESERTA DIDIK DI MUSLIM SUKSA SCHOOL THAILAND (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the number wheel media on students' learning activity in mathematical addition operations at Muslim Suksa School Thailand. The background of this study is the low learning activity of students in mathematics learning, especially in the material of addition operations, so that interesting and innovative learning media are needed to increase student involvement. This study uses a quantitative approach with an experimental method, using a pre-test and post-test design for one group. The sample in this study amounted to 20 students. Data collection techniques were carried out by observation, while data analysis used descriptive and inferential statistics with paired sample t-test. The results of the study showed that the average learning activity of students before using the number wheel media was 16.00, while after the application of the number wheel media increased to 24.10. The results of the normality test showed that the data were normally distributed with a significance value of more than 0.05. Furthermore, the results of the paired sample t-test showed a significance value of 0.001 <0.05. Therefore, there is a significant influence between the use of number wheel media on student learning activity. Based on the results of this study, it can be concluded that there is an influence of number wheel media on student learning activity in mathematical addition operations at Muslim Suksa School, Thailand. Therefore, the use of innovative and interactive learning media is highly recommended to improve the quality of mathematics learning.